THE INTEGRATION OF THE KWL (KNOW, WANT, LEARN) STRATEGY AND THE ZOOM CONFERENCE IN TEACHING READING: AN ACTION RESEARCH - HASTOMO, TOMMY; ZULIANTI, HAJJAH (Linguists : Journal of Linguistics and Language Teaching, 2022)
This research aimed to improve the students’ reading comprehension by using the Know Want Learn (KWL) strategy. The objectives of this research were to investigate whether the integration of the Know Want Learn (KWL) strategy in the Zoom conference can improve the students’ reading comprehension and identify the students' perception of using the KWL Strategy in the Zoom conference. In this research, the researchers used classroom action research as the research design in collecting the data. The research was conducted in three cycles. The samples of this research were 30 students. The researchersemployedquestionnaire, observation and test for the data collecting technique. The test used in this research was reading test consisted of 25 questions. The researchers used descriptive analysis for analyzing the data. The findings of this research show that the integration of the Know Want Learn (KWL) strategy in the Zoom conference successful to improve students’ reading comprehension and reading activity. The improvement of students’ reading comprehension can be concluded from the mean score of the pre-test is 65.42and the mean score of the post-test is 85.49. Moreover, there are 26% (8) students who show moderate perception, 24% (7) students offer positive perceptions, and 50% (15) students show very positive perceptions.Furthermore, the combination of KWL Strategy and Zoom conference can help students achieve the learning target. The students can get many benefits from using this combination to study English. They also can conduct an effective teaching-learning activity in a modern way even though they are not allowed to attend the face-to-face classroom.